Asymmetry Inside The Symmetry: Mechanisms and Disorders Of Laterality - Alanay, Yasemin; Gümüş, Ersin; Sekkin, Miray; Güler, Sebile; Çakar, Nur (Gynecology Obstetrics & Reproductive Medicine, 2006)
Asymmetry of the left-right (L-R) axis is a feature of vertebrates that is apparent in the viscera and vasculature. An understanding of L-R patterning in human dev elopment is aided by familiarity with key events and important pathways in mammalian embryogenesis.The induction of L-R asymmetry follows the establishment of the anteroposterior (A-P or rostrocaudal) and dorsov entral (D-V) axes and requires the pre-existing midline symmetry to be broken before sidedness is induced via a series of complex, coordinated molecular signaling events. In this review, our aim is to describe the molecular background of this embryological process, and give brief knowledge concerning its clinical consequences.